Impact of High-Risk Characteristics in Hypoplastic Left Heart Syndrome. Issue 4 (July 2019) - Salve, Gananjay G.; Datar, Gauri M.; Perumal, Gopinath; Singh, Aakansha Ajay Vir; Ayer, Julian G.; Roberts, Philip; Sholler, Gary F.; Cole, Andrew D.; Pigott, Nick; Loughran-Fowlds, Alison; Weatherall, Andrew; Alahakoon, T. Indika; et al.
Background: Management of hypoplastic left heart syndrome (HLHS) presents many challenges. We describe our institutional outcomes for management of patients with HLHS over the past 12 years and highlight our strategy for those with highly restrictive/intact interatrial septum (R/I-IAS). Methods: Eighty-eight neonates with HLHS underwent surgical treatment, divided equally into Era-I (n = 44, April 2006 to February 2013) and Era-II (n = 44, March 2013 to June 2018). Up to 2013, all patients with R/I-IAS were delivered at an adjacent adult hospital and then moved to our hospital for intensive care and management. From 2014, these patients were delivered at a co-located theatre in our hospital with immediate atrial septectomy. The hybrid approach was occasionally used with preference for the Norwood procedure for suitable candidates. Results: One-year survival after Norwood procedure was 62.5% and 80% for Era-I and Era-II ( P = not significant (ns)), respectively, and 41% of patients were categorized as high risk using conventional criteria. Survival at 1 year differed significantly between high-risk and standard-risk patients ( P = 0.01). For high-risk patients, survival increased from 42% to 65% between eras ( P = ns). In the R/I-IAS subgroup (n = 15), 11 underwent Norwood procedure after emergency atrial septectomy. Of these, seven born at the adjacent adult hospital had 40% survival to stage II versus 60% for the four born at the colocated theatre. Delivery in a colocated theatre reduced the birth-to-cardiopulmonary bypass median time from 445 (150-660) to 62 (52-71) minutes. Conclusion: Reported surgical outcomes are comparable to multicenter reports and international databases. Proactive management for risk factors such as R/I-IAS may contribute to improved overall outcomes.